MARLINA: POLEMIK KE-SUBJEK-AN DALAM SASTRA DAN MEDIA - Sholih, Mohammad Badrus (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
In a literary work, there is the desire of the character in it, and also the desire of the author which is listed and becomes the fulfillment of his desire. For Lacan, the fulfillment of desires is a process to achieve an authentic and whole subject. However, this is a complicated problem when it comes to dealing with and entering into a symbolic order. The film “Marlina The Killer of Four Acts” is one of the films that portray the problematics of the subject in a symbolic order so that it triggers the writer to understand the problem of subjectivity using Jacques Lacan's psychoanalytic theory. There are problems that the author wants to answer regarding the subject of Marlina, namely, 1) how is the image of the desire of the subject of Marlina displayed? 2) what is the desire of the film writer? and 3) what is the correlation with the media apparatus? This research uses the Lacanian psychoanalytic method to find answers to the problems of the subject in Marlina's character. The authors get results in the form of 1) how the image obtained by Marlina is identification in the mirror phase formed by language contaminated by other desires, thus making Marlina have a jouissance to get out of the symbolic order and achieve an authentic subject 2) also how the film's author's desire is a desire contained in the character of Marlina, and 3) how the media becomes a castration of the author's desire that prevents the author from achieving wholeness in his subject.